A new species of Raveniola Zonstein, 1987 (Araneae, Nemesiidae) from Fujian, China - Guchun Zhou; Jian Lu; Muqiushi Cui; Jiasheng Xu (Biodiversity Data Journal)
The genus Raveniola Zonstein, 1987 comprises 66 species, distributed across regions from East Asia to the Caucasus, with about 20 species recorded from China. According to Zonstein et al. (2018) and Zonstein (2024), members of Raveniola can be identified by the presence of two to three retroventral megaspines arranged sequentially on tibia I in males and paired spermathecae in females, each bearing two-branched heads or a lateral diverticulum.A new mygalomorph species, Raveniola fuzhouensis Zhou, sp. nov., is described from Fujian Province, China. Detailed description, diagnosis, illustrations and a distribution map of the new species are provided.